PENGARUH UKURAN PERUSAHAAN DAN LIKUIDITAS TERHADAP STRUKTUR MODAL DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2010-2014) - Umam, Muchamad Chaerul; Mahfud, M. Kholiq (Faculty of Economics and Business Diponegoro University, 2016)
The capital structure is one of complex financial decision as it relates to other financial decision variables. This study aimed to examine the effect of firm size and liquidity to capital structure by using profitability as an intervening variable. Log Natural Total Assets (SIZE) is used as a proxy for the size of the company, Current Ratio (CR) is used as a proxy for liquidity, Return on Assets (ROA) is used as a proxy for profitability and Debt to Equity Ratio (DER) is used as a proxy for capital structure.This study uses 40 manufacturing companies listed in Indonesian Stock Exchange during the period 2010-2014 as the sample. Determination of the samples was done by purposive sampling method. The analysis technique used is path analysis using computer software programs such as AMOS 20.0. Next, sobel test is used in the interest to test the strength of the indirect effect of independent variables on the dependent variable through intervening variable.The results showed that SIZE have no significant effect on ROA, while CR have significant positive effect on ROA. SIZE have significant positive effect on DER, while CR and ROA have significant negative effect on DER. Furthermore, sobel test results showed that ROA can not mediate the effect of SIZE to DER, while the ROA may mediate the effect of CR to DER.